A new hybrid technique using low salinity water injection and foam flooding for enhanced oil recovery in sandstone rock - Shabib-Asl, A. (2019)
Foam flooding has been applied to improve oil recovery. However, interactions between crude oil and foam destabilize the foam and reduce its efficiency. Many researchers have examined the effects of interactions between crude oil and foam with a focus on the negative effects of these interactions. The goal of this study is to investigate the potential of a new hybrid Enhanced Oil Recovery (EOR) method termed Low Salinity Water Assisted Foam flooding (LSWAF) in sandstone rocks. This method involves the injection of Low Salinity Water (LSW) followed by the alternate injection of a Surfactant Aqueous Solution (SAS) and CO2 gas. LSW solutions were prepared using different salinities of NaCl, KCl, CaCl2, and MgCl2. Experiments were carried out using two types of crude oil with a different Total Base Number (TBN) and Total Acid Number (TAN), namely crude oil A and B. In terms of changes in wettability, for both crude oils, the experimental results revealed that the test with LSW of 500 ppm KCl outperformed other salinities. For crude oil with a higher TBN, the proposed hybrid technique led to improved performance. The insights presented in this study provide a good reference for further research in this area. Â© 2018 Elsevier B.V.